The decreasing prevalence of nonrefractive visual impairment in older Europeans: a meta-analysis of published and unpublished data - Delcourt, Cécile; Mirshahi, Alireza (Ophthalmology, 2018)
Topic - To estimate the prevalence of nonrefractive visual impairment and blindness in European persons 55 years of age and older. - Clinical Relevance - Few visual impairment and blindness prevalence estimates are available for the European population. In addition, many of the data collected in European population-based studies currently are unpublished and have not been included in previous estimates. - Methods - Fourteen European population-based studies participating in the European Eye Epidemiology Consortium (n = 70 723) were included. Each study provided nonrefractive visual impairment and blindness prevalence estimates stratified by age (10-year strata) and gender. Nonrefractive visual impairment and blindness were defined as best-corrected visual acuity worse than 20/60 and 20/400 in the better eye, respectively. Using random effects meta-analysis, prevalence rates were estimated according to age, gender, geographical area, and period (1991-2006 and 2007-2012). Because no data were available for Central and Eastern Europe, population projections for numbers of affected people were estimated using Eurostat population estimates for European high-income countries in 2000 and 2010. - Results - The age-standardized prevalence of nonrefractive visual impairment in people 55 years of age or older decreased from 2.22% (95% confidence interval [CI], 1.34-3.10) from 1991 through 2006 to 0.92% (95% CI, 0.42-1.42) from 2007 through 2012. It strongly increased with age in both periods (up to 15.69% and 4.39% in participants 85 years of age or older from 1991 through 2006 and from 2007 through 2012, respectively). Age-standardized prevalence of visual impairment tended to be higher in women than men from 1991 through 2006 (2.67% vs. 1.88%), but not from 2007 through 2012 (0.87% vs. 0.88%). No differences were observed between northern, western, and southern regions of Europe. The projected numbers of affected older inhabitants in European high-income countries decreased from 2.5 million affected individuals in 2000 to 1.2 million in 2010. Of those, 584 000 were blind in 2000, in comparison with 170 000 who were blind in 2010. - Conclusions - Despite the increase in the European older population, our study indicated that the number of visually impaired people has decreased in European high-income countries in the last 20 years. This may be the result of major improvements in eye care and prevention, the decreasing prevalence of eye diseases, or both.
Gesehen am 11.03.2021